Twinning the Goals : How Can Promoting Shared Prosperity Help to Reduce Global Poverty? - Lakner, Christoph; Negre, Mario; Prydz, Espen Beer (World Bank Group, Washington, DC, 2014)
In 2013, the World Bank adopted two goals: First, reduce global extreme poverty to 3 percent by 2030. Second, promote shared prosperity defined as the income growth of the bottom 40 percent of the population within a country. This paper simulates the global poverty headcount under three growth scenarios for the bottom 40 percent up to 2030. The analysis deploys a set of "shared prosperity premiums," in which the bottom 40 percent in each country grows at a differential rate from the projected growth in the mean. With no distributional change, the global headcount reaches between 6.7 and 4.7 percent in 2030, depending on the average growth scenario used for the simulations. However, if the incomes of the bottom 40 percent grow 2 percentage points faster than the mean, the World Bank's poverty goal is achieved with the global poverty falling to below 3 percent in 2030 in the scenarios which average growth rates are extrapolated from the early 2000s. While such a "shared prosperity premium" is not unprecedented in recent growth spells, maintaining it over 20 years in every country is optimistic. The paper shows that in the baseline growth scenario, the global poverty rate could either reach the 3 percent target, or be close to 10 percent, depending on the "shared prosperity premium."